Craft sects in the city of Jeddah in the 14th century AH/20 AD - Al-Sabban, Abeer Othman (Journal of Humanities & Social Sciences, 2024)
The city of Jeddah had a strategic location in the middle of the eastern coast of the Red Sea, which had a direct impact on the economy of its people. They worked in trade, crafts, and handicrafts, as they were mostly crafts inherited from family and grandparents. The study proved that the craft organization of craftsmen in the city of Jeddah witnessed a clear progression among the people of Jeddah. Crafts and crafts. There is the sect’s sheikh, the teacher, and the boy (the craftsman), and the development of these organizations led to the existence of a special system or custom that guarantees the owners of crafts protection from members of the same sect or from competing sects.
Keywords: Jeddah city; fourteenth century AH; economy; crafts; handicrafts